2022
DOI: 10.1186/s13148-022-01231-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal alcohol exposure with offspring DNA methylation in mammals: a systematic review of the evidence

Abstract: Background Prenatal alcohol exposure (PAE) is associated with a range of adverse offspring neurodevelopmental outcomes. Several studies suggest that PAE modifies DNA methylation in offspring cells and tissues, providing evidence for a potential mechanistic link to Fetal Alcohol Spectrum Disorder (FASD). We systematically reviewed existing evidence on the extent to which maternal alcohol use during pregnancy is associated with offspring DNA methylation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…Expression of circHomer1 was intermediate in adult occipital cortex and hippocampus, with the lowest levels detected in adult SAC cerebellum (Figure 2A). Previous studies have shown H19 is a prenatal stage-enriched lncRNA important for embryogenesis (Poirier et al, 1991;Gabory et al, 2009;Li et al, 2019) and previously implicated in FASD (Marjonen et al, 2017(Marjonen et al, , 2018Bestry et al, 2022). However, its expression was still detectable in the adult brain in our control SAC brain samples, with higher levels in the cerebellum and lower expression in the adult frontal cortex (Figure 2B), which is the opposite of what was observed for circHomer1.…”
Section: Opposing Brain Region-and Developmental-specific Changes In ...contrasting
confidence: 81%
See 3 more Smart Citations
“…Expression of circHomer1 was intermediate in adult occipital cortex and hippocampus, with the lowest levels detected in adult SAC cerebellum (Figure 2A). Previous studies have shown H19 is a prenatal stage-enriched lncRNA important for embryogenesis (Poirier et al, 1991;Gabory et al, 2009;Li et al, 2019) and previously implicated in FASD (Marjonen et al, 2017(Marjonen et al, , 2018Bestry et al, 2022). However, its expression was still detectable in the adult brain in our control SAC brain samples, with higher levels in the cerebellum and lower expression in the adult frontal cortex (Figure 2B), which is the opposite of what was observed for circHomer1.…”
Section: Opposing Brain Region-and Developmental-specific Changes In ...contrasting
confidence: 81%
“…Interestingly, H19 has been reported to have sex-specific expression and to be differentially affected by estrogen and androgen treatment (Sun et al, 2015;Basak et al, 2018;Ozgur and Gezer, 2020;Li T. et al, 2021). Moreover, H19 has been previously linked with changes in head circumference in FASD and reported to be epigenetically altered in various tissues (Marjonen et al, 2017(Marjonen et al, , 2018Bestry et al, 2022). Taken together, this allows us to hypothesize that PAE could induce epigenetic changes in the H19 locus in a sex-specific manner, which could result in opposing changes in circHomer1 expression.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Folic acid (FA) is a dietary methyl donor for DNA methylation [133], while vitamin B12 is a cofactor involved in the process of transferring the methyl group from FA to DNA [134]. FA has been widely used in the clinic for DR treatment, while studies suggest that low FA levels can result in both hypomethylation and hypermethylation, leading to misregulation of DNA methylation [27,135].…”
Section: Targeting Methyl Donors For Dna Methylation: Folic Acid and ...mentioning
confidence: 99%